2011
DOI: 10.1590/s0103-65132011005000033
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de apreçamento de opções embutidas em produtos de previdência no Brasil

Abstract: Este artigo apresenta um modelo para determinação do passivo e do risco financeiro associado às opções implícitas atreladas a produtos de previdência complementar no Brasil (PGBL/VGBL). Propõe-se uma modelagem específica para o problema através da caracterização da opção financeira embutida nos produtos de previdência com possibilidade de conversão do saldo final do participante em benefício vitalício sob termos predeterminados. Modelam-se também as características financeiras desse passivo, tais como duração,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…If they decide to be subject to regressive taxation, policyholders may choose to replace the traditional progressive taxation that applies increasing marginal rates of up to 27.5% according to the revenue bracket. Authors such as Saad and Ribeiro (2011) and, recently, Martins and Campani (2019), have pointed out a gap in studies investigating the choice between progressive and regressive forms of taxation. Therefore, a relevant line of research emerges from the opportunity to optimize taxation, maximize net wealth, and add gains to the amounts received from retirement benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If they decide to be subject to regressive taxation, policyholders may choose to replace the traditional progressive taxation that applies increasing marginal rates of up to 27.5% according to the revenue bracket. Authors such as Saad and Ribeiro (2011) and, recently, Martins and Campani (2019), have pointed out a gap in studies investigating the choice between progressive and regressive forms of taxation. Therefore, a relevant line of research emerges from the opportunity to optimize taxation, maximize net wealth, and add gains to the amounts received from retirement benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of both studies suggested a preference for fixed-income funds with Fábio Garrido Leal Martins / Carlos Heitor Campani scheduled withdrawals, suggesting avoiding exercising the option for a retirement annuity. Saad and Ribeiro (2011) presented a theoretical model to assess liabilities and financial risks related to PGBL and VGBL retirement annuity as a call option. Melo and Melo (2009) calculated through micro-simulation that the actuarial annuity for lifetime retirement can have a positive net present value if postponed for over 70-year-olds since favorable parameters are in place (the life table and a real interest rate of 3% in the benefits phase or 50% surplus reversal).…”
Section: Introductionmentioning
confidence: 99%